Digital transformation as an adaptation factor for personnel to realise productive capacity in a pandemic - S. V. Koblov (Вестник университета)
The directions for the development of the enterprise digital environment are considered, and the ways to improve the professional competences of the enterprise staff, including the digital aspect, have been analysed. A questionnaire survey of the personnel of the Central Research Institute of Mechanical Engineering in 2019 and 2020 using the methodology “Assessment of personnel capability (Manageability Assessment)” revealed the problems determined by the digital transformation process. Significant components for staff have been identified, including clarity of understanding of their place in the project, appreciation of task setting, staff focus on the overall end result, and functional interpersonal interaction. In analysing levels of manageability levels, the influence on the staff labor activity the factors such as remuneration, social and living conditions in the enterprise, ergonomic conditions at the workplace, interpersonal horizontal and vertical relationships in the team, and social effectiveness of management, have been studied. The findings provide the basis for practical recommendations to Central Research Institute of Mechanical Engineering management on changing the enterprise organisational culture to activate the staff labor potential. This solved the problems identified, improving the efficiency of staff working remotely in a pandemic and the manageability of staff across the enterprise as a whole.